Permainan Olahraga Tradisional SMAN 1 Polewali Mandar - M. Said Zainuddin; Yasriuddin Yasriuddin; Arifuddin Usman; Ahmad Zakaria; Ikhwan Abduh (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The Community Diversity Program implemented at SMAN 1 Polewali Mandar aims to address the issue of disparities and boredom in students' learning that often occur in school. Through this program, students will be given the opportunity to play simple, innovative, and challenging traditional games. This is expected to revive their interest in learning and make them more ready and motivated to continue their studies after a break. The program will last for 240 minutes and will use a hands-on approach and lecture method. In the hands-on session, students will play traditional sports games and are expected to be physically active, thus improving their gross motor development. This program will also enhance students' understanding of conventional sports games and provide them with the opportunity to create traditional games as creative and enjoyable learning materials. This community literacy program is very important for students' development as the physical activities performed during the program will help improve their physical condition, making them fresher and more enthusiastic to continue their studies. It is hoped that this will motivate them to be more active and enthusiastic in learning and participating in other school activities